Epstein-Barr Virus Reactivation after Infliximab in Rheumatoid Arthritis: A Case Report. (30th June 2011) - Colaci, Michele; Sebastiani, Marco; Sandri, Gilda; Meacci, Marisa; Ferri, Clodoveo
Abstract : TNF-alpha blockers represent one of the most important therapeutic strategies for rheumatoid arthritis, but their use has raised the question about their safety profile, particularly in respect to viral infections/reactivations. We describe the case of a patient who developed a symptomatic EBV reactivation 11 days after the first infusion of infliximab.